Clinical and Hematological Parameters Study of sheep infected by Theileria SPP - A., AL–Amiry A.M. (The Iraqi Journal of Veterinary Medicine, 2001)
A Study of clinical and haematological changes in Awassi stock of sheep that had schizonts of Theileria spp. In Abu – Greeb region were conducted. Seventy three blood samples were collected from jugular vein of different ages, 60 had schizonts indicating an infection rate 82.19%. There were no great evidence of variation in clinical and haematological features between infected and non infected sheep.